2006
DOI: 10.1051/0004-6361:20054539
|View full text |Cite
|
Sign up to set email alerts
|

Study of FK Comae Berenices

Abstract: Aims. Time-series spot modelling was used to follow the longitude changes of active regions responsible for the light variability of FK Com between 1987Com between −2004. Methods. The photometric data are analysed in the time-series mode of a spot modelling code. A scenario of one polar and two low-latitude active regions (hereafter spots, for simplicity) depicts the light variations very well. The role of the polar spot remains unclear because photometry in general does not provide direct latitudinal surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 18 publications
11
52
0
Order By: Relevance
“…One dominant cycle is present in the record changing smoothly between 4.5 and 6.1-yr. This is consistent with the earlier result by Oláh et al (2006), who found quasiperiods of about 5.2 and 5.8-yr in the longitudes of starspots, based on a record of 18 years, between JD 2 446 800-53 200 (1987-2004).…”
Section: Figsupporting
confidence: 93%
“…One dominant cycle is present in the record changing smoothly between 4.5 and 6.1-yr. This is consistent with the earlier result by Oláh et al (2006), who found quasiperiods of about 5.2 and 5.8-yr in the longitudes of starspots, based on a record of 18 years, between JD 2 446 800-53 200 (1987-2004).…”
Section: Figsupporting
confidence: 93%
“…It is not clear whether or not these different types of events are caused by the same phenomenon or not. A similar type of two-fold behaviour of ab-and gr-events has been reported in FK Com, by Oláh et al (2006) and Hackman et al (2013), for instance.…”
Section: Active Longitudes and Flip-flop Eventssupporting
confidence: 80%
“…The appearance of spots between the active longitudes resembles what Oláh et al (2006) found in photometry of FK Com and called phase-jumps. In a phase-jump, old active areas disappear and then new ones emerge, with an offset of roughly 90…”
Section: Active Longitudes and Flip-flop Eventssupporting
confidence: 70%
“…Oláh et al (2006) find that both flip-flops and phase jumps can be found on FK Com. They conclude that these are two different, although possibly connected phenomena.…”
Section: Introductionmentioning
confidence: 81%